Pengaruh Citra Institusi, Harga dan Lokasi terhadap Keputusan Memilih Universitas Swasta di Bandung - Ezra Karamang; Eka Septiarini; Palupi Permata Rahmi; Fanji Wijaya (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
The objective of this research is to explore how institutional image, price, and location influence students' decisions when selecting private universities in Bandung City. This study aims to provide deep and relevant insights for the development of effective student recruitment strategies. The research employs a quantitative method with a verificative analysis technique to describe both partial and simultaneous influences. Sampling was conducted using a purposive sampling technique through the distribution of questionnaires, direct observations, and interviews with students from private universities in Bandung. Based on predetermined criteria, from the entire population of 2043 respondents, a total of 244 samples were deemed suitable for use in this study. The partial T-test results confirm that institutional image and price have a strong influence on students' decisions to choose private universities in Bandung, while location does not have a significant impact. Simultaneously, the F-test indicates that institutional image, price, and location significantly influence students' decisions. In conclusion, the regression model used meets various classical assumptions, and the variables studied have a strong influence on students' decisions when selecting private universities in Bandung.